2017
DOI: 10.1073/pnas.1618991114
|View full text |Cite
|
Sign up to set email alerts
|

Providing driver’s licenses to unauthorized immigrants in California improves traffic safety

Abstract: The integration of immigrants presents a major challenge for policymakers in the United States. In an effort to improve integration, several US states recently have implemented laws that provide driver's licenses to unauthorized immigrants. These new laws have sparked widespread debate, but we lack evidence on the traffic safety impact of these policies. We examine the short-term effects of the largest-scale policy shift, California's Assembly Bill 60 (AB60), under which more than 600,000 licenses were issued … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 14 publications
2
36
0
2
Order By: Relevance
“…The Institute for Social Research (2018) also exploited the fact that California's UILP was likely felt more intensely in counties with the most unauthorized immigrants. In contrast to Lueders, Hainmueller, and Lawrence (2017), the Institute for Social Research (2018) did not find any relationship between AB 60 licenses for unauthorized immigrants and hit-and-run collisions when they measured exposure using the share of the county comprised of unauthorized immigrants. The authors speculated that while gaining a license may have initially increased unauthorized immigrants' willingness to interact with law enforcement officials, this effect was offset by the 2016 presidential election and the Trump administration's immigration priorities.…”
Section: Unauthorized Immigrants and Traffic Outcomesmentioning
confidence: 96%
See 1 more Smart Citation
“…The Institute for Social Research (2018) also exploited the fact that California's UILP was likely felt more intensely in counties with the most unauthorized immigrants. In contrast to Lueders, Hainmueller, and Lawrence (2017), the Institute for Social Research (2018) did not find any relationship between AB 60 licenses for unauthorized immigrants and hit-and-run collisions when they measured exposure using the share of the county comprised of unauthorized immigrants. The authors speculated that while gaining a license may have initially increased unauthorized immigrants' willingness to interact with law enforcement officials, this effect was offset by the 2016 presidential election and the Trump administration's immigration priorities.…”
Section: Unauthorized Immigrants and Traffic Outcomesmentioning
confidence: 96%
“…Using the eventstudy specification from Equation (2), we show in Figure 3 that UILPs are unrelated to the number of licensed drivers in the preimplementation 13. In Table A3 (Supporting information) we analyze the relationship between California's UILP-known as AB 60-and collisions using the SWITRS data and methodology of Lueders, Hainmueller, and Lawrence (2017). First, we descriptively show that AB 60 increased the number of licensed drivers in Figure A1 (Supporting information).…”
Section: Uilps and Driving Behaviormentioning
confidence: 99%
“…Research has shown that effective countermeasures to hit-and-run accidents include driver education campaigns similar to those used to reduce drunk driving, reducing the incentive to flee (Lueders, Hainmueller, & Lawrence, 2017) and raising public awareness of the high likelihood of getting caught. Providing trace evidence analyses in your jurisdictions and broadcasting the successes in solving hit-and-run accidents will increase submission of essential trace evidence by crime scene investigators and may, in fact, motivate drivers not to run after a crash, thereby providing the opportunity to render aid to an injured victim and potentially save lives.…”
Section: José R Almirallmentioning
confidence: 99%
“…Si les sans-papiers obtiennent ainsi un droit d'accès au permis de conduire, il s'agit toutefois d'un droit dont les conséquences sont soigneusement encadrées. Parmi les quelques 10.5 millions de sans-papiers21 qui vivent et résident aux États-Unis, nombreux sont ceux disposant d'un permis de conduire dans leur pays d'origine et ayant l'habitude de conduire aux États-Unis22 . Dans les États qui autorisent déjà les étrangers en situation irrégulière à conduire, il a été démontré que ce type de mesure tendait au contraire à renforcer la sécurité routière23 .…”
unclassified
“…Dans les États qui autorisent déjà les étrangers en situation irrégulière à conduire, il a été démontré que ce type de mesure tendait au contraire à renforcer la sécurité routière23 . Une étude menée en Californie démontrait également que cette mesure incitait à l'immatriculation des véhicules ainsi qu'une diminution des délits de de fuite en cas d'accidents24 , d'où la nécessité de limiter la communication des données des personnes sans-papiers aux agences d'application des lois migratoires afin d'éviter les risques de fuites. À New York, les retombées économiques attendues ne sont par ailleurs pas négligeables et ont certainement pesé dans l'adoption d'une telle mesure.…”
unclassified